Art, violence and memory in Taiwan: Telling the story of the beautiful island. (June 2018) - Harrison, Mark
Taiwan is a liminal site of modernity in Asia. It is a modern exemplar as a liberal democracy with a developed economy, but is mostly unrecognized as a nation-state in the international system. In its liminality, however, it traces contours of modern power and their epistemological expression. This paper presents an account of Taiwan as an object of knowledge and representation in instances of scholarship and policy, Taiwanese politics, urban development and art, arguing that the narratives through which Taiwan is understood embed a lived experience as Taiwanese under forms of epistemological domination. The paper then explores Taiwanese responses of co-option and resistance in alternative sites of knowledge, and it concludes that the critical unexamined force in Taiwan's experience of modernity is violence.